MUTASI: BENTUK SANKSI DI BIDANG KEPEGAWAIAN? - Cahyadini, Amelia; Radjab, Abi Ma’ruf; Pinky, Chyntia (Faculty of Law, Parahyangan Catholic University, 2020)
In the civil servant management system, developed on the basis of merit system, any official can be at any time be transferred, promoted or demoted. In practice this option may and have often been misused as tool in office politics to remove troublesome civil servant. From the civil servant’s perspective, the options open are either comply or decline the standing order and face the consequence of disciplinary sanction. This article shall discuss, using a legal/juridical normative method, legal aspects of this management tool. The aim is to propose a guidance for civil servants on how to deal with orders of transfer or motion/demotion.